C-Hyp: a combined wave and wind energy platform with balanced contributions - Soulard, Thomas; Babarit, Aurélien; Borgarino, Bruno; Mickael, Wyns; Harismendy, Migel (Volume 8: Ocean Renewable Energy, 2014)
Volume 8: Ocean Renewable EnergyNantes, France, June 9–14, 2013Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-5542-3 International audience This paper synthesizes the technical feasibility study carried out for a hybrid ocean energy converter, with balanced wind and wave contributions. The solution envisaged involves a 100m diameter circular barge equipped with floating oscillating wave surge converters (OWSCs). This floating structure is mounted with a 5MW wind turbine. The present study covers power performance estimations, structural analysis and mooring design calculations. The first section describes the “Wave to Wire” model programmed in both frequency and time domain. The mathematical and hydrodynamic assumptions are highlighted together with the numerical model. The second part starts with the assessment of the performances of this device, carried out on in-house simulation codes. Based on combined wave and wind resources, the annual average absorbed power figures are compared with published results for existing ocean energy converters. The total rated power of the combined system reaches 10MW. Eventually, the last section approaches practical topics, directly related to the capital and operational costs inherent to an industrial development phase. The total steel mass is estimated first, from structural calculations carried out for a selection of 3D static loads cases. Then, a technical solution for the mooring system is presented together with the envisaged installation procedure.